Pengaruh Fraksi Volume terhadap Kekuatan Tarik Komposit Hibrid Serat Gambas (Luffa Cylindrica) dan Fiberglass - Syahdila Yoga Pratama; Deni Andriyansyah (Pusat riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of varying hybrid composite volume fractions of luffa (Luffa cylindrica) fiber and fiberglass on the tensile strength of the material. The composite matrix used was polyester resin, while the reinforcements consisted of luffa fibers treated with 5% KOH alkaline solution to improve adhesion with the matrix, and fiberglass as an additional strengthening material. The composition variations applied in this research were 90%:5%:5%, 85%:7.5%:7.5%, and 80%:10%:10% (polyester resin : luffa fiber : fiberglass). The fabrication process was carried out using the hand lay-up method, which is widely used for producing layered composites, followed by tensile testing according to standard mechanical testing procedures to evaluate tensile strength and elongation. The results showed that the addition of luffa fiber and fiberglass fractions had a significant influence on the mechanical properties of the composites. The 80%:10%:10% variation demonstrated the highest tensile strength value of 13.65 MPa and the highest elongation of 0.0105%, indicating better mechanical performance compared to other variations. These findings confirm that the hybridization of natural luffa fiber and synthetic fiberglass can work synergistically to improve the tensile strength of the composite. However, higher fiber fractions should be considered carefully, as they may affect the homogeneity of the mixture and the quality of interfacial bonding. Further research is recommended to optimize volume fractions, enhance fiber surface treatments, and evaluate additional mechanical properties such as impact strength and hardness, in order to explore the potential of hybrid composites as eco-friendly materials with promising mechanical performance.